2018
DOI: 10.1111/aogs.13390
|View full text |Cite
|
Sign up to set email alerts
|

Fetal heart rate short term variation during labor in relation to scalp blood lactate concentration

Abstract: In the early stages of intrapartum hypoxia, STV increases, contrary to findings regarding chronic hypoxia in the antenatal period. The increase in the adrenergic surge is a likely explanation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Intriguingly, the findings that have emerged to date from large retrospective and prospective clinical studies 4,66 are not consistent with some of the guiding principles of CTG. For example, the majority of acidemic fetuses do not show suppressed FHR variability, and can even show increased FHR variability 4,15,[67][68][69] . Moreover, the morphological or timing-based classification of decelerations is not associated with acidemia (cord pH < 7.1), but in contrast the assessment of the depth and duration of all decelerations via metrics such as 'total deceleration area' or 'deceleration capacity' is associated with acidemia 4,15,34,67 .…”
Section: Fetal Physiology In the Era Of Big Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, the findings that have emerged to date from large retrospective and prospective clinical studies 4,66 are not consistent with some of the guiding principles of CTG. For example, the majority of acidemic fetuses do not show suppressed FHR variability, and can even show increased FHR variability 4,15,[67][68][69] . Moreover, the morphological or timing-based classification of decelerations is not associated with acidemia (cord pH < 7.1), but in contrast the assessment of the depth and duration of all decelerations via metrics such as 'total deceleration area' or 'deceleration capacity' is associated with acidemia 4,15,34,67 .…”
Section: Fetal Physiology In the Era Of Big Datamentioning
confidence: 99%
“…With these caveats in mind, it is striking that the lessons learned from these animal studies have converged with the lessons from recent clinical studies. For example, animal studies reveal that the regulation of FHR variability during labor is complex and cannot be reduced to a binary system in which high equals good and low equals bad 71,72 , paralleling the inconsistent predictive value of FHR variability in clinical studies 4,15,[67][68][69] . Modern understanding of the fetal peripheral chemoreflex (the response to hypoxemia) and the fetal baroreflex also concludes that the peripheral chemoreflex is the most likely mediator of the vast majority of intrapartum decelerations 71 , while the common belief that many decelerations are explained by baroreflex activation is in fact false (discussed in detail in 71 ).…”
Section: Fetal Physiology In the Era Of Big Datamentioning
confidence: 99%
“…Antenatally, FHRV is used to assess fetal health and to monitor cases at risk of fetal growth restriction (1)(2)(3), and its potential to identify prior antenatal hypoxia-ischemia (HI) has recently been explored (4). During labor, fetal heart rate (FHR) and FHRV are used to assess the risk of acute HI (5)(6)(7)(8)(9). There is increasing interest in the use of neonatal heart rate variability (HRV) to help identify neonates who have suffered acute intrapartum HI and may benefit from therapeutic hypothermia (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent large cohort studies have found that FHRV in labor does not discriminate between acidotic and nonacidotic cases (6,7). Furthermore, increased intrapartum STV has been associated with increased fetal scalp lactate levels (32), and increased FHRV on visual inspection was associated with an increase in risk of acidemia at birth (39). Systematic studies in fetal sheep have demonstrated that fetal compromise can be associated with both increased and suppressed FHRV (12,17,26,31,49).…”
Section: Introductionmentioning
confidence: 99%